Quality of life of dengue patients in Panembahan Senopati regional general hospital - Wigatiningtyas, Ariska; Perwitasari, Dyah Aryani; Faridah, Imaniar Noor; Dania, Haafizah; Supadmi, Woro (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
Yogyakarta is one of the top 10 cities with the highest number of dengue cases in Indonesia. One of the reasons for this is the lack of knowledge about the dengue virus in the community. To find out the quality of life of dengue patients in the Bantul Penembahan Senopati Public Hospital.This research uses the descriptive method with a cross-sectional design. The sampling technique utilized was the purposive sampling method. 18 research subjects were chosen as the sample with an inclusion criteria of patients undergoing inpatient treatment and aged > 4 years of age. This study used the EQ-5D-5L and EQ-5D-Y.The quality of life of 70% of the adult patients experienced pain of EQ-VAS 67 ± 17.191, while all child patients experienced pain of EQ-VAS 54.375 ± 11.783. The quality of life of dengue patients was measured with the EQ-5D-5L for adults and EQ-5D-Y for children and obtained a poor score due to a decrease in the dimension of pain felt and the usual activities done such as working, studying, and playing.